Content analysis of fluoride-related posts on Instagram - Fatemeh Esmaeilzadeh; Taraneh Movahhed; Mohammad Reza Hasani Yaghooti; Melika Hoseinzadeh; Saber Babazadeh (BMC, 2024)
Abstract Background The Internet and social media have become many people's primary sources of health information. Instagram is one of the most popular social media platforms, and users spend a significant amount of time daily on the platform. Therefore, analyzing oral health-related information shared online can help to identify the requirements of specific groups, assisting in the planning and execution of educational public health actions. As a result, this study was carried out to conduct a qualitative evaluation of fluoride-related content on Instagram in 2022-2023. Methods Using hashtags associated with fluoride, a search was conducted on the Instagram application in the Persian language. All fluoride-containing posts were saved, and data was collected thrice at two-month intervals. MAXQDA software version 2020 was used to categorize the collected data content based on type, quality, and quantity. Results The qualitative analysis included 1565 (9.45%) posts with fluoride-related content out of 16,475 total posts. After removing the duplicates, 400 posts remained, among which 282 posts (70.5%) and 118 posts (29.5%) were pro- and anti-fluoride, respectively. After qualitative analysis, 270 codes were examined and categorized into three main themes and eight subthemes: "fluoride sources," "The advantages and disadvantages of fluoride," and "Invalid beliefs about fluoride." Conclusion The frequency of pro-fluoride use was higher than anti-fluoride posts. However, due to the high prevalence of posts containing false information on fluoride toxicity for health, ineffectiveness on caries prevention, and conspiracy theories, there is a need to improve the quality of information on fluoride by providing scientific and unbiased explanations by professionals online or during dental visits and supervising social media content.